Double-mode absorption in subwavelength grating with loaded graphene-dielectric stacking. (April 2020) - Bian, Li-an; Hong, Yingjie; Li, Gaosheng; Liu, Zhu; Pan, Shaopeng; Shen, Wanting
Abstract: Double-mode absorption is obtained theoretically at terahertz frequencies based on one subwavelength grating with loaded graphene-dielectric stacking (GDS). At approaching critical coupling or impedance matching, these modes realize near-unity absorption under the joint action of Fabry-Perot (FP) resonance and Fano resonance. Relying on the simulation method of rigorous coupled-wave analysis, it is found that both modes are sensitive to the chemical potential of graphene. Also, the peak-peak distance can be controlled by changing the grating geometry, the period of GDS and the angle of incident light. Besides, the modes number is subject to the embedding position of GDS. In brief, this proposed absorber should be useful to detect adjacent incident lights, sense smartly incoming-wave signals and response in large dynamic range. Highlights: Double-mode absorption is obtained based on one subwavelength grating with loaded graphene-dielectric stacking. Near-unity absorption is realized for graphene-dielectric stacking without maximal localized electric field. Modes-shift is independent against the change of grating geometry and the period of graphene-dielectric stacking. The modes number is subject to the embedding position of graphene-dielectric stacking.